2020
DOI: 10.3389/fphar.2020.00665
|View full text |Cite
|
Sign up to set email alerts
|

Precision Dosing of Doxapram in Preterm Infants Using Continuous Pharmacodynamic Data and Model-Based Pharmacokinetics: An Illustrative Case Series

Abstract: Conclusion: Real-time and non-invasive effect monitoring of drug therapy combined with model-based exposure provides relevant information to clinicians and can importantly improve therapy. The variability between and within patients emphasizes the importance of individual, objective evaluation of pharmacotherapy. These measurements, together with data on ADRs, allow for precision medicine in neonatology that should be brought to the bedside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…[49] It is however also suggested to be effective in reducing the number of apnoea and desaturations in preterm infants[8, 9, 50], although this effect is not observed in every infant treated with doxapram. [51] Decades ago, small randomized controlled trials compared doxapram with either placebo or theophylline without evaluating the long-term effects. [52][53][54][55] An observational study found a higher cumulative doxapram dosage in preterm infants with neurodevelopmental impairment compared to matched controls with a normal mental development, although this association could be confounded by indication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[49] It is however also suggested to be effective in reducing the number of apnoea and desaturations in preterm infants[8, 9, 50], although this effect is not observed in every infant treated with doxapram. [51] Decades ago, small randomized controlled trials compared doxapram with either placebo or theophylline without evaluating the long-term effects. [52][53][54][55] An observational study found a higher cumulative doxapram dosage in preterm infants with neurodevelopmental impairment compared to matched controls with a normal mental development, although this association could be confounded by indication.…”
Section: Discussionmentioning
confidence: 99%
“…[57] The rate of apnoea and hypoxic events can also uctuate largely within and between patients, and detection can be di cult. [51,58] We therefore chose for a more pragmatic design with less strict inclusion criteria. The decisions to start doxapram in routine clinical care, to adjust its dosage, or to stop doxapram therapy are made by the attending physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our population PK model serves to predict the exposure to doxapram and keto-doxapram in individual patients. By integrating continuous physiological PD data with model-based drug exposure and data on adverse drug reactions (ADRs), we might set one step towards precision medicine in neonatology, as has been illustrated by Poppe et al 40 ADRs are also important to take into account as the use of one bodyweight-based dosage may have led to overexposure to doxapram in a proportion of this vulnerable population in the past. This may have increased the frequency of ADRs that have been reported in preterm infants, including QT interval lengthening 41 possibly resulting in an atrioventricular heart block, 42 gastrointestinal problems, 41,43 tachycardia, 23 increased electroencephalographic activity and less sleep-wake cycling, 44 irritability and agitation, 23,43 and hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“… 37 In the field of pharmacology, recent analysis of electronically captured vital signs has begun to demonstrate the potential vital signs data have for better informing drug provision and dosing in neonatal units. Poppe et al 38 retrospectively identified responders and nonresponders to doxapram therapy (a respiratory stimulant sometimes used as an adjunct to caffeine therapy for the treatment of apnea of prematurity, though not currently recommended for routine use due to limited evidence of efficacy and safety), 39 and those infants who were overexposed and risked unnecessary adverse effects. Interestingly, their case series also presented infants who may have unnecessarily started doxapram despite clinical review of observational charts at the time suggesting its indication, highlighting the disadvantage of intermittent review of vital signs.…”
Section: Vital Signs—an Underutilized Resource?mentioning
confidence: 99%